2017
DOI: 10.4314/njp.v44i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis B surface antigenaemia among secondary school students in Abakaliki, South Eastern Nigeria

Abstract: Abstract:Background: Majority of secondary school students are adolescents; an age group with a tendency to engage in healthcompromising risky behaviours in order to deal with anxiety and gain admission to peer groups. This exposes them to risk of Hepatitis B virus infection which is a major public health concern globally and in Nigeria.Objectives: This study focuses on some common risky behavioural practices that characterize the lifestyle of contemporary adolescent subculture; with a view to determining thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…The investigated risk factors such as unsafe injection practices, sharing of sharp objects, genital circumcision, blood transfusion, sexual exposure/abuse, previous surgical operation, and scarification/tattoo in the current study showed no significant association with the prevalence of HBsAg and HCV infection in either HIV-infected or HIV naïve children. This is in concordance with a previous report by earlier researchers [ 6 , 27 , 42 , 58 ]. The rationale behind these findings could be due to current ongoing awareness and adoption of healthy lifestyles, preventive measures by the population, the robust national blood transfusion program, and better access to health care services.…”
Section: Discussionsupporting
confidence: 94%
“…The investigated risk factors such as unsafe injection practices, sharing of sharp objects, genital circumcision, blood transfusion, sexual exposure/abuse, previous surgical operation, and scarification/tattoo in the current study showed no significant association with the prevalence of HBsAg and HCV infection in either HIV-infected or HIV naïve children. This is in concordance with a previous report by earlier researchers [ 6 , 27 , 42 , 58 ]. The rationale behind these findings could be due to current ongoing awareness and adoption of healthy lifestyles, preventive measures by the population, the robust national blood transfusion program, and better access to health care services.…”
Section: Discussionsupporting
confidence: 94%
“…As expected, malaria was the leading cause of paediatric admissions during the course of the tool implementation. Manifestations of severe malaria and its complications including cerebral malaria, prostration, severe malaria anaemia, and complex febrile convulsions were consistent with findings of similar studies conducted in malaria endemic countries in sub-Saharan Africa [18, 23, 28-30]; and lend credence to a WHO report that progress in malaria control has stalled despite the considerable achievements recorded in the last two decades. [36]…”
Section: Discussionsupporting
confidence: 84%
“…WFH <-2SD), and having at least one danger sign were risk factors for death among the children. These factors resonate with findings of similar studies conducted in Africa [18, 22, 23] and underscore the need for improved nutritional support for children and better health-seeking behaviours of parents and caregivers of under-five children.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations